Implementasi Kebijakan Stimulus Perekonomian Sebagai Countercycical dalam Upaya Menyelamatkan Pelaku Pariwisata Terdampak Covid-19 di Kabupaten Badung - I Gusti Agung Ayu Yuliartika Dewi; Ida Bagus Gde Indra Wedhana Purba (Program Studi Administrasi Negara, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Warmadewa, 2022)
Tourism has become a mainstay sector in development in the Province of Bali. The contribution of tourism to the economy is quite high. At the end of 2019 tourist visits and international tourists experienced a significant decline due to the Covid-19 pandemi which caused the collapse of Bali tourism, especially in Badung Regency as a major tourist destination. Facing an increasingly difficult economic situation amid the outbreak of the Corona virus, the Financial Services Authority has begun to implement a policy of providing stimulus to the economy with the issuance of POJK No.11/POJK.03/2020 National Economic Stimulus as a Countercyclical Policy as a result of the spread of Covid-19 This POJK is expected to be a policy that is able to maintain economic stability and maintain economic growth for the Balinese people, most of whom are engaged in the tourism sector, especially in Badung Regency. This research uses qualitative research methods with descriptive research type. Primary data obtained through the process of observation, interviews, and documentaries. The selection of informants was done by purposive sampling. Data validation is done by triangulation of data sources so that the data presented is valid data. The results of this study describe the implementation of the policy stimulus as a countercyclical in an effort to prevent tourism actors causing the COVID-19 pandemi and describe the supporting and inhibiting factors of this policy.